Core Configuration Effect On The Flexural Behaviour Of Sandwich Panel Made Of Aluminium Skin And Sengon Wood Core - Jauhar Fajrin; Ni Nyoman Kencanawati; Miko Eniarti; Arismanto Arismanto (Civil Engineering Departement, Andalas University, 2021)
Among the many choices of composite sandwich panel cores, Balsa wood is one of the main alternatives of cores made of wood. However, the availability and price of Balsa wood are quite expensive, so it needs alternatives from other types of wood such as Sengon wood. The purpose of this study was to evaluate the feasibility of Sengon wood as a core of composite sandwich panels. Three variations of the Sengon wood layout had been prepared as the core of the sandwich panels with a skin made of aluminum. All specimens, including the control specimens made of whole Sengon wood, were prepared with a size of 550 x 50 x 24 mm for length, width, and depth, respectively. Each variation and also the control specimens were made of 3 pieces. Tests were carried out based on the ASTM C 393-94 standard under the three-point bending test scheme. The results showed that the sandwich panel with plain Sengon wood core has the highest capacity to carry a flexural load, which is approximately 177.391 MPa, followed by a sandwich panel with long and end grain Sengon board that possess flexural strength of 153.913 MPa and 79.101 MPa, respectively. The flexural strength of these sandwich panels is superior to solid Sengon wood. The sandwich panels showed a typical ductile material indicated by a non-linear curve without a distinct yielded point before reach the maximum failure load. Three sandwich panels with various Sengon wood cores collapsed under three types of failure mechanisms; face wrinkling, shearing of the core, and delamination between the interface of skin and core. In conclusion, Sengon wood has a great potential to be used as the core material for a composite sandwich panel.